Penerapan Model Pembelajaran Kontekstual Untuk Meningkatkan Pemahaman Konsep Peserta Didik Pada Materi Ipa Di Kelas V Sd Negeri 143 Tetehaka - Eka Avrilyana Husaini; Arna Juwairiyah; Ahmad Ahmad (Jurnal Sultra Elementary School, 2021)
The application of the Contextual Teaching and Learning (CTL) model aims to improve students’ conceptual understanding in science subjects for fifth-grade students at SD Negeri 143 Tetehaka. This research was supervised by Arna Juwairiyah, S.Pd., M.Pd. as the first supervisor and Ahmad, S.Pd., M.Pd. as the second supervisor. The study was conducted due to the following issues: (1) students’ learning outcomes were still low—many students had difficulty understanding science concepts, as shown by their average daily test scores of 50 (on a scale of 0–100), which were far below the mastery threshold of 65; and (2) the learning process was dominated by lecture-based methods, making students less interested and less involved in learning activities, which resulted in weak conceptual understanding.The purpose of this research was to determine how the implementation of the contextual learning model could enhance students’ conceptual understanding in science. This study employed a quantitative approach with the type of Classroom Action Research (CAR). The data collection techniques used were observation and tests. The results showed that in the first cycle, the percentage of students achieving mastery was 46.66% in the first meeting and 53.33% in the second meeting, with an average class score of 62.29. In the second cycle, the percentage of students achieving mastery increased to 73.33% in the first meeting and 80% in the second meeting, with an average class score of 73.43.These findings indicate that the implementation of the Contextual Teaching and Learning (CTL) model can effectively improve students’ conceptual understanding in science learning.